2001
DOI: 10.1001/jama.285.19.2474
|View full text |Cite
|
Sign up to set email alerts
|

Surgery vs Orthosis vs Watchful Waiting for Hallux Valgus

Abstract: Surgical osteotomy is an effective treatment for painful hallux valgus. Orthoses provide short-term symptomatic relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
138
0
6

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(148 citation statements)
references
References 12 publications
4
138
0
6
Order By: Relevance
“…Deformity of the great toe nail, splaying of the forefoot and problems with shoe fitting may also be observed. These problems can lead to considerable pain, gait abnormalities, functional limitations, balance disorders, and increase the risk of falling in the elderly (1,3,4,6,8,(13)(14)(15)(16)(17). Furthermore, some studies have found that people with hallux valgus score poorly on evaluations of health-related quality of life (4).These findings suggest that hallux valgus does not simply cause isolated problems in the feet but can have a broader effect on the individual as a whole (5).…”
Section: Introductionmentioning
confidence: 99%
“…Deformity of the great toe nail, splaying of the forefoot and problems with shoe fitting may also be observed. These problems can lead to considerable pain, gait abnormalities, functional limitations, balance disorders, and increase the risk of falling in the elderly (1,3,4,6,8,(13)(14)(15)(16)(17). Furthermore, some studies have found that people with hallux valgus score poorly on evaluations of health-related quality of life (4).These findings suggest that hallux valgus does not simply cause isolated problems in the feet but can have a broader effect on the individual as a whole (5).…”
Section: Introductionmentioning
confidence: 99%
“…(45,46) The distal metatarsal osteotomy in our study was a minimally invasive, simple bony procedure without other advanced soft tissue procedures. We did not perform bunion resection, formal capsulorrhaphy, lateral release or capsulotomy.…”
Section: Discussionmentioning
confidence: 98%
“…In advanced phase of HV corrective surgery is mostly indicated [11]. Surgical osteotomy is found to be an effective treatment for painful advanced phase HV, while orthoses provide short-term symptomatic relief [13].…”
Section: Introductionmentioning
confidence: 99%